The Role of Interleukin-1 cytokine family (IL-1β, IL-37) and interleukin-12 cytokine family (IL-12, IL-35) in eumycetoma infection pathogenesis. - Amir Abushouk; Amre Nasr; Emad Masuadi; Gamal Allam; Emmanuel E Siddig; Ahmed H Fahal (Public Library of Science (PLoS), 2019)
Mycetoma is a neglected tropical disease, endemic in many tropical and subtropical regions, characterised by massive deformity and disability and can be fatal if untreated early and appropriately. Interleukins (IL) -35 and IL-37 are newly discovered cytokines that play an important role in suppressing the immune system. However, the expression of these interleukins in patients with Madurella mycetomatis (M. mycetomatis) induced eumycetoma has not yet been explored. The aim of this study is to determine the levels of IL-1 family (IL-1β, IL-37) and IL-12 family (IL-12, IL-35) in a group of these patients and the association between these cytokines levels and the patients' demographic characteristics. The present, case-control study was conducted at the Mycetoma Research Centre, Soba University Hospital, University of Khartoum, Sudan and it included 140 individuals. They were divided into two groups; group I: healthy controls [n = 70; median age 25 years (range 12 to 70 years)]. Group II: mycetoma patients [n = 70 patients; median age 25 (range 13 to 70 years)]. Cytokines levels were measured in sera using enzyme linked immunosorbent assay (ELISA). There was a significant negative correlation between IL-1β and IL-12 levels and lesion size and disease duration, while IL-37 and IL-35 levels were significantly positively correlated with both lesion size and disease duration. The analysis of the risk factors of higher circulatory levels of IL-37 in patients of mycetoma showed a negative significant association with IL-1β cytokine, where a unit increment in IL-1β will decrease the levels of IL-37 by 35.28 pg/ml. The levels of IL-37 among the patients with a duration of mycetoma infection ≤ 1 year were significantly low by an average of 18.45 pg/ml compared to patients with a mycetoma infection's duration of ≥ 5years (reference group). Furthermore, the risk factors of higher levels of IL-35 in mycetoma patients revealed a negative significant association with IL-12, as a unit increment in IL-12 decreases the levels of IL-35 by 8.99 pg/ml (p < 0.001). Levels of IL-35 among the patients with duration of mycetoma infection ≤ one year were significantly low on average by 41.82 pg/ml (p value = 0.002) compared to patients with a duration of mycetoma infection ≥ 5 years (reference group). In conclusion, this study indicates that both IL-35 and IL-37 are negatively associated with the levels of IL-1β and IL-12 in eumycetoma mycetoma infection; and high levels of IL-37 and IL-35 may have a negative impact on disease progression.